PERAN LABA MEMODERASI HUBUNGAN MODAL KERJA DAN BIAYA EKUITAS (Studi Kasus pada Perusahaan Manufaktur di Bursa Efek Indonesia) - Ratnawati, Ratnawati (Students Journal of Economic and Management, 2012)
This study aimed to examine the effect of Nibe to Working Capital Gain and equity costs of case studies on the effects of manufacturing companies on Bursa Efek Â Indonesia (BEI). The samples used in this research is a group of companies manufacturing the category of companies whose shares are actively traded on the Stock Exchange always during peeode observations (2007-2010). The number of samples obtained by category amounted to 19 companies over a period of 4 years. Secondary data was obtained from the Indonesia Stock excange (IDX) annual statistics for the period 2007 to 2010. The analysis used in this study is multiple regression techniques (multiple regression) to test the hypothesis t-test and F-test at the 5% level of significance (Î± = 0.05). Hypothesis test results indicate that the variable income and variable working capital Nibe together equally significant effect on the cost of equity. This result indicates that these two variables are jointly able to significantly influence the cost of equity. The test results also found that working capital and cost of equity has a negative and significant effect, because it has the value of the Standardized Beta Coefficiens 0000 0601 and its significance is greater than alpha (0.05). Keywords: Nibe earnings, working capital, cost of equity